Cell cycle arrest and apoptosis- inducing effect of Dicranopteris linearis (Burm.F.) Underw. leaf crude extract in MDA-MB-231 cell - Baharuddin, Aifaa Akmal (2018)
Dicranopteris linearis is a common species of fern locally known to the Malays as ‘Resam’. Scientifically, the plant has been reported to have antinociceptive, antiinflammatory, antipyretic, chemopreventive and antioxidant properties which can be linked to its potential to treat various kinds of ailments including inflammatoryrelated diseases and cancer. Nevertheless, its anticancer potential has not been extensively investigated. This study was done to evaluate the cytotoxic activities of D. linearis extracts against several cancer cell lines, to observe the morphological changes on MDA-MB-231 cells, to determine the cell cycle arrest induction in MDA-MB-231 cells and to analyze the mode of cell death in MDA-MB-231 cells. MTT assay was used to determine the cytotoxic effects of Methanol (MEDL) and petroleum ether (PEEDL) extracts of D. linearis at concentration of 100, 50, 25, 12.5, 6.25 and 3.125 μg/mL against a panel of cancer cell lines namely breast adenocarcinomas (MCF-7 and MDA-MB-231), cervical adenocarcinoma (HeLa), colon carcinoma (HT-29), hepatocellular carcinoma (HepG2) and lung carcinoma (A549) for 72 hours period of incubation. MTT results were compared with cancer cells that were not pretreated with MEDL and PEEDL and cancer cells that were treated with 5-fluorouracil (5-FU) as the positive drug control group. Mouse fibroblast cells (3T3) were used to observe the cytotoxic effect of MEDL and PEEDL against the normal cells. Data indicated that MEDL showed the most significant cytotoxicity effect against MDA-MB-231 cell at IC50 value of 22.4 μg/mL while PEEDL does not show cytotoxic effect against all of the cancer cells. MEDL also showed selective cytotoxic activity against the proliferation cancer cells (MDAMB- 231, HeLa and MCF-7) and did not harm the normal mouse fibroblast (3T3) cells. MEDL was able to inhibit the growth of MDA-MB-231 cell in a time dependent manner after incubation period of 24, 48 and 72 hours which showed that MEDL was able to prevent recurrent of cancer cells growth during the incubation period. Phase contrast microscopy examinations showed that MEDL was able to induce apoptosis in MDA-MB-231 cell which was characterized by the presence of cell shrinkage, cell rounding, cell detachment and membrane blebbing. AOPI fluorescence microscopy examinations showed that there were presence of early apoptotic, late apoptotic and necrotic cells in MDA-MB-231 cells that were treated with MEDL after 24, 48 and 72 hours. Quantitative AOPI results showed that MEDL could induce apoptosis in MDA-MB-231 cell line in a time-dependent manner. Result showed that the percentage of early apoptotic cells increased significantly (p < 0.05) from 8.17% to 8.67% to 11.83% at 24, 48 and 72 hours, respectively. The percentage of late apoptotic cells was also seen to increase significantly (p < 0.05) from 10.67% to 11.17% to 17.50% at 24, 48 and 72 hours, respectively. As for the necrotic cells, the percentage was also seen to increase significantly (p < 0.05) from 5.50% to 16.00% to 24.00% at 24, 48 and 72 hours, respectively. Cell cycle analysis revealed that MEDL induced S phase cell cycle arrest in MDA-MB-231 cell effectively where the percentage of cells in the S phase was seen to increase significantly (p<0.05) from 32.58% at 24 hours to 55.82% at 48 hours and 69.62% at 72 hours. The proportion of cells in the S phase increased significantly (p<0.05) compared to the untreated cells and 5-FU treated cells. Early apoptosis induction in MDA-MB-231 cell was confirmed by Annexin V-FITC and Propidium Iodide (PI) staining. After 24 and 48 h of treatment with MEDL, the proportion of early apoptotic cells reduced from 6.60% to 5.87% at 24 and 48 h, respectively. Following this, the proportion of the late apoptotic cells in the MEDL treated group at 24 and 48 h increased significantly (p < 0.05) with values of 8.47% and 12.37%, respectively when compared to the untreated cells and 5-FU treated cells. These findings suggested that MEDL has the potential to be developed as a potent cytotoxic agent against MDA-MB-231 cancer cell line as well as complied with the regulation and halal requirements which is safe to be used since it does not harm the normal cells.